2018
DOI: 10.3390/rs10060904
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Decadal Groundwater Changes in African Sedimentary Aquifers Estimated Using GRACE Products and LSMs

Abstract: Increased groundwater abstraction is important to the economic development of Africa and to achieving many of the Sustainable Development Goals. However, there is little information on long-term or seasonal groundwater trends due to a lack of in situ monitoring. Here, we used GRACE data from three products (the Centre for Space Research land solution (CSR), the Jet Propulsion Laboratory's Global Mascon solution (JPL-MSCN), and the Centre National D'etudes Spatiales / Groupe de Recherches de Géodésie Spatiale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 73 publications
(109 reference statements)
3
38
0
Order By: Relevance
“…poor functionality rates, with less than 50% of hand pumps equipped boreholes fully functional in Ethiopia (Kebede et al 2017) with similar results for other African countries (Mwathunga et al 2017, Owor et al 2017. Reasons for poor functionality are complex with poor siting, maintenance and corrosion (Foster 2013, Fisher et al 2015, Bonsor et al 2018 often being cited as greater predictors of failure than drought. The implications are clear, ensuring that households have access to a well sited borehole equipped with a handpump, and investing in maintenance to improve functionality, is an excellent way to improve access to secure water through extended dry seasons and drought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…poor functionality rates, with less than 50% of hand pumps equipped boreholes fully functional in Ethiopia (Kebede et al 2017) with similar results for other African countries (Mwathunga et al 2017, Owor et al 2017. Reasons for poor functionality are complex with poor siting, maintenance and corrosion (Foster 2013, Fisher et al 2015, Bonsor et al 2018 often being cited as greater predictors of failure than drought. The implications are clear, ensuring that households have access to a well sited borehole equipped with a handpump, and investing in maintenance to improve functionality, is an excellent way to improve access to secure water through extended dry seasons and drought.…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater offers storage of a different magnitude than annual rainfall or river flow (MacDonald et al 2012) and across the African continent appears resilient to droughts of several years. No significant longterm regional decline in groundwater storage has been observed over the past 20 years (Bonsor et al 2018) despite shorter term variability (Kolusu et al 2019) and longer term decline (>1000 years) associated with increasing aridity from longer climate process across northern African aquifer basins (e.g. Gossel et al 2004, Edmunds 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown recharge to be episodic in semi-arid regions of Africa (Meyer, 2005;van Wyk et al, 2011;Taylor et al, 2013;Cuthbert et al, 2017) and elsewhere (Jasechko and Taylor, 2015;Cuthbert et al, 2016), highlighting the need to understand patterns and drivers of climate variability, both temporally and spatially, that influence recharge. Bonsor et al (2018Bonsor et al ( ) analysed recent (2002Bonsor et al ( -2016 trends in, and seasonality of, groundwater storage within 12 African sedimentary basins implied from Gravity Recovery and Climate Experiment (GRACE) satellite data. Here, we employ evidence from both in situ observations (piezometry) and GRACE satellite data to examine the effect of large-scale inter-annual climate anomalies on groundwater across spatial scales for locations and domains that represent the rainfall anomaly gradient over EASE and SA associated with characteristic El Niño response, exemplified by the event of 2015-2016.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that there is relatively poor correlation between GRACE and GHMs/LSMs in the evaluation of ∆TWS, with significant discrepancies at the basic level of whether storage trends are increasing or decreasing (Scanlon et al, 2018). These findings have been confirmed with reference to regional piezometric groundwater measurements from tropical aquifers in Africa (Bonsor et al, 2018). Thus, the application of GRACE 90 data to ∆GWS implies three distinct areas of uncertainty: in the processing of the GRACE signal, accuracy of GHM/LSM model projections and mutual consistency of the observed (GRACE) and modelled (GHM/LSM) data (Long et al, 2015).…”
mentioning
confidence: 76%
“…Several studies have used GRACE data to examine storage changes within a particular GW system e.g. Bonsor et al, 2018;Chen et al, 2016Chen et al, , 2010Henry et al, 2011;Z. Huang et al, 2015;Ramillien et al, 2014;Shamsudduha et al, 2017Shamsudduha et al, , 2012Tiwari et al, 2009;Xavier et al, 2010;Yeh et al, 2006).…”
mentioning
confidence: 99%